2012
DOI: 10.1007/s11250-012-0308-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation in early growth traits, litter size, and lamb survival in two Iranian fat-tailed sheep breeds

Abstract: In the present study, 1,635 lambing records of Ghezel (n=766) and Mehraban (n=869) breeds were used to evaluate the early growth traits, litter size, and lamb survival in sheep reared in Fars Province, southern Iran, during a 5-year-long period. The least squares means (± SE) of lamb birth weight for Ghezel were 5.27 (± 0.22), 5.02 (± 0.22), and 3.98 (± 0.23) kg for single males, single females, and twin lambs, respectively; whereas, the corresponding values for Mehraban were 4.39 (± 0.18), 4.18 (± 0.18), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…This is in agreement with results of Matos et al (1993), who found that males and females have similar survival rates, but it does not agree with previous studies both in wool (Sawalha et al, 2007;Hatcher et al, 2009;Everett-Hincks et al, 2014) and hair sheep (Holmøy et al, 2012;Hinch and Brien, 2014), where male lambs had higher mortality than females. Contrary to the above-mentioned studies, Atashi et al (2013) found that Iranian male lambs showed higher survival rate than females. It could be that Katahdin dams are not drastically affected by the greater size and weight at birth of male lambs, which leads to longer labor, compared to females (Dwyer, 2003) and eventually tend to have higher mortality than females.…”
Section: Discussioncontrasting
confidence: 74%
“…This is in agreement with results of Matos et al (1993), who found that males and females have similar survival rates, but it does not agree with previous studies both in wool (Sawalha et al, 2007;Hatcher et al, 2009;Everett-Hincks et al, 2014) and hair sheep (Holmøy et al, 2012;Hinch and Brien, 2014), where male lambs had higher mortality than females. Contrary to the above-mentioned studies, Atashi et al (2013) found that Iranian male lambs showed higher survival rate than females. It could be that Katahdin dams are not drastically affected by the greater size and weight at birth of male lambs, which leads to longer labor, compared to females (Dwyer, 2003) and eventually tend to have higher mortality than females.…”
Section: Discussioncontrasting
confidence: 74%
“…The low pre-weaning mortality rate of 4% obtained in this study was a remarkable feat. Reported pre-weaning mortality rates varied from as low as 1.79% (Swarnkar et al 2019) through 3-10% (Atashi et al 2013;Chauhan et al 2019) to 11-19.7% (Abdelqader et al 2017;Elia 2018;Khan et al 2006;Mustafa et al 2014;Snyman 2010). The significantly high average birth weight (95.3% of all offspring were > 3 kg), small litter size (63.5%, singleton births), and predominantly summer lambing/kidding (59.66%) are all possible explanations for the rather low mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al (2010) [5] reported an overall mortality rate of 4.48% in a Sirohi goat field flock, while Snyman (2010) [11] observed a rate of 11.50% in Angora goats. Comparative findings show slightly higher mortality rates in studies by Mandal et al (2005) [7] (6.6% in Muzaffarnagari sheep), Atashi et al (2013) [2] (7.1% in Ghezel sheep), Mustafa et al (2014) [8] (7.3% in Pak Karakul, 11.2% in Thali sheep, 14.2% in Kacchi sheep), Getachew et al (2015) [3] (12.2% in Menz sheep), Abegaz et al (2000) [1] (8.8% in Menz sheep), Soundarajan et al (2014) [12] (27.89% in Madras red sheep), and Thiruvenkadan et al (2003) [14] (40.51% in Mecheri sheep). The highest pre-weaning mortality among Sirohi goat kids occurred in the year 2004 (19.35%), while the lowest was recorded in the year 2013 (1.77%).…”
Section: Pre-weaning Mortality (0-3 Months)mentioning
confidence: 67%